Chemical composition, antioxidant and hypolipidaemic properties of red seaweed, Gracilaria changii - Chan, Pei Teng (2014)
The objectives of this study were to evaluate the chemical composition and in vitro antioxidant activities of red seaweed, Gracilaria changii grown in Malaysia, investigate effects of this seaweed on cholesterol lowering, antioxidant enzymes activities and the effects on biomarkers, morphological and histological characteristics on selected organs of hyperlipidaemia and normal rats.Edible red seaweed, G. changii, collected from the coastal area of Sarawak, Malaysia, was evaluated for its antioxidant activities using a range of in vitro assays namely 2,2,- diphenyl-1-picrylhydrazyl (DPPH), beta-carotene bleaching (BCB), and ferric reducing power (FRAP) assays. The total phenolic and total flavonoids content were also determined. The results showed that G. changii contains high dietary fibre (64.74 %), protein (12.57 %), and low in Na/K ratio (0.12). Among the various extracts (ethanol, methanol, acetone, ethyl acetate, water) evaluated on their antioxidants activities, ethyl acetate extract showed good radicals scavenging effect and reducing power. The total phenolic (21.75 mg PGE/g extract) and flavonoids (200.87 mg RE/g extract) content of ethyl acetate extract was also highest amongst the extracts studied. The hypolipidaemic effect of G. changii was evaluated on high cholesterol/fat (HF) induced and normal (NF) rats. Seven groups of ten rats each were fed for eight weeks: [1] normal control (NF), [2] NF+5% G. changii powder, [3] NF+10% G. changii powder, [4] HF, [5] HF+5% G. changii powder, [6] HF+10% G. changii powder, [7] positive control (HF+Atorvastatin). The HF diet group showed a significantly higher value of total cholesterol (TC), low density lipoprotein (LDL-C), atherogenic index (AI) and body weight gain as compared to others treatment groups. At week 8, rats were fed with HF diet supplementing with 10% seaweed powder significantly lowered the plasma TC, LDL-C, and TG content by -40.34 %, -35.95 %, and -30.91 % respectively, compared to the HF group. Supplementation of G. changii to atherogenic diet also improved the erythrocytes enzymes antioxidant activity (SOD, CAT, and GSH-Px) by reducing lipid peroxidation. Diets supplementing with seaweed powder showed no abnormalities in the organs gross morphology, somatic index and biomarkers, indicating that G. changii does not caused toxicity effect to the hyperlipidaemia and normal rat’s organs during experimental period. Histological findings showed that G. changii supplemented group able to ameliorate the histological changes of the hyperlipidaemic rat’s liver cells, less hepatic steatosis and inflammatory infiltrate was observed compared to the untreated rats. In conclusion, G. changii has a remarkable hypolipidaemic action in an animal model of dietary induced hyperlipidaemia and may contribute to a reduction of CVDs risk and probably be put forward for potential application as a functional food ingredient for human consumption.